Physical examination of the shoulder an evidence-based approach - Warth, Ryan J.; Millett, Peter J. (Springer, 2015)
Physical Examination of the Shoulder will serve as an invaluable resource for practicing orthopedic surgeons, sports medicine specialists, physical therapists, residents in training and medical students interested in the field of clinical orthopedics.